Does the Internet Promote Collaboration and Productivity? Evidence from the Scientific Community in South Africa - R. Sooryamoorthy and Wesley Shrum (Journal of Computer-Mediated Communication, 12(2), 2007, 2007)
International collaboration among scientists has been passionately advocated by many in the developing world. Among the several conditions that support collaboration among members of a dispersed scientific community, Internet technology is crucial. We examine the relationships among electronic communication, collaboration, and productivity in South Africa, a country that has undergone remarkable change in the sphere of science and technology. We surveyed 275 scientists in selected research institutes and universities in the province of KwaZulu-Natal to address the questions: Is greater use of the Internet associated with international collaboration? Are collaboration and Internet use associated with publication in national and foreign journals? The results show that: (1) Internet use, as measured by time spent on email, is positively associated with collaboration; (2) collaboration is not generally related to publication productivity; and (3) there is little evidence that South African academics benefit from international collaboration. While scientists who use email intensively are slightly more productive, this is not the case for foreign productivity in the case of academic scientists.